A conceptual model for advancing university branding: Focusing on cognitive dimensions - Torabi, Hassan; Hosnavi, Reza; Nezhad, Faezeh Yousef; Azadi , Akbar; Haghi, Masoud (International Journal of Financial, Accounting, and Management, 2025)
Purpose: This study aims to develop a conceptual model for enhancing university branding by examining the role of key cognitive components. It provides practical insights for academic institutions to strengthen their brand positioning in a competitive educational landscape. Research Methodology: This study adopted an applied research design utilizing a descriptive survey method. Data were collected from faculty members and students at a public university in Tehran through standardized questionnaires. Structural Equation Modeling (SEM) was implemented using Smart PLS software to examine relationships between cognitive components including brand image, trust, communication, service quality and loyalty and their influence on university branding. Results: The results revealed that brand loyalty and brand communication are the most influential factors in university branding. Brand loyalty had the highest impact, followed by communication. The study confirmed that strengthening cognitive elements significantly improves brand positioning and interested party engagement. Conclusions: Cognitive components, particularly brand loyalty, communication, trust and service quality, play a critical role in university branding. Strategic efforts to build positive perceptions, foster trust and maintain consistent communication are essential for enhancing brand reputation and attracting students. Limitations: The study was confined to a single university in Tehran, Iran and relied on self-reported data, potentially introducing bias. It also excluded emotional and behavioral factors and its cross-sectional design limits longitudinal insights. Contribution: The study offers a validated model demonstrating how cognitive factors enhance university branding, providing actionable strategies for academic institutions.